Prolonged podocyte depletion in larval zebrafish resembles mammalian focal and segmental glomerulosclerosis - Hansen, Kerrin Ursula Ingeborg; Siegerist, Florian; Daniel, Sophie; Schindler, Maximilian; Iervolino, Anna; Blumenthal, Antje; Daniel, Christoph; Amann, Kerstin Ute; Zhou, Weibin; Endlich, Karlhans; Endlich, Nicole (The FASEB Journal, 2020)
Focal and segmental glomerulosclerosis (FSGS) is a histological pattern frequently found in patients with nephrotic syndrome that often progress to end-stage kidney disease. The initial step in development of this histologically defined entity is injury and ultimately depletion of podocytes, highly arborized interdigitating cells on the glomerular capillaries with important function for the glomerular filtration barrier. Since there are still no causal therapeutic options, animal models are needed to develop new treatment strategies. Here, we present an FSGS-like model in zebrafish larvae, an eligible vertebrate model for kidney research. In a transgenic zebrafish strain, podocytes were depleted, and the glomerular response was investigated by histological and morphometrical analysis combined with immunofluorescence staining and ultrastructural analysis by transmission electron microscopy. By intravenous injection of fluorescent high-molecular weight dextran, we confirmed leakage of the size selective filtration barrier. Additionally, we observed severe podocyte foot process effacement of remaining podocytes, activation of proximal tubule-like parietal epithelial cells identified by ultrastructural cytomorphology, and expression of proximal tubule markers. These activated cells deposited extracellular matrix on the glomerular tuft which are all hallmarks of FSGS. Our findings indicate that glomerular response to podocyte depletion in larval zebrafish resembles human FSGS in several important characteristics. Therefore, this model will help to investigate the disease development and the effects of potential drugs in a living organism.
CRIS-Team Scopus Importer:2020-10-23
Keywords: FSGS; glomerulus; podocyte injury; zebrafish model organism